Migratory songbirds and urban window collision mortality: vulnerability depends on species, diel timing of migration, and age class - Olivia M. Colling; Christopher G. Guglielmo; Simon J. Bonner; Yolanda E. Morbey (Avian Conservation and Ecology, 2022)
Hundreds of millions of birds are estimated to die annually in North America by colliding with windows, and understanding the species-level correlates of collision mortality is an important step towards mitigation. We used a 16-year window collision dataset for 35 migratory songbird species from Toronto's (Canada) Fatal Light Awareness Program (FLAP) to quantify species differences in vulnerability to urban window collision mortality and potential correlates during the autumn period by applying generalized linear models. To control for annual abundance, we used migration monitoring data from two stations. Our index of vulnerability was the catch ratio, defined as the ratio of annual catch-per-unit effort in each station's mist net program to annual catch-per-unit effort in FLAP. Catch ratios varied among species with Ovenbird (Seiurus aurocapilla), Common Yellowthroat (Geothlypis trichas), and Lincoln's Sparrow (Melospiza lincolnii) being most vulnerable to window collision mortality and Blue-headed Vireo (Vireo solitarius), Yellow-rumped Warbler (Setophaga coronata), and Ruby-crowned Kinglet (Regulus calendula) being least vulnerable. Foraging guild had a minor effect on the catch ratio, but species with a propensity for nocturnal migration had lower catch ratios (greater vulnerability) than those that did not. Based on a subset of species (n = 4) and years (n = 2), hatch-year birds were overrepresented relative to after-hatch-year birds in FLAP compared to the nearby migration monitoring station in 3 of 4 species. This study provides the first ranked list of species vulnerability to urban window collision mortality for songbirds migrating through downtown Toronto, provides evidence that juveniles are more vulnerable to window collision mortality than adults in some species, and highlights the need for more comparative studies of migratory movement behavior to investigate why some species are more vulnerable to urban window collision mortality than others.